FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA UKM SENTRA BANDENG KELURAHAN TAWANG MAS SEMARANG - Utami, Ratih Hesty; Indiworo, Rr. Hawik Ervina (Business Management Analysis Journal (BMAJ), 2019)
The marketing ability of a company can affect its financial capabilities. One of the company's benefits can be generated from the demand for products and / or services, and other business functions will not run if there is no demand. a company must obtain revenue if it wants profit. One of the elements to get income is from marketing products and / or services. The marketing mix is a collection of controlled tactical marketing tools that companies combine to produce the responses they want in the target market. The marketing mix consists of all the things a company can do to influence the demand for its products. These possibilities can be grouped into four groups. Among them are Products (Price), Price (Price), Place (Place), and Promotion (Promotion). In this study 100 respondents were used. Determination of sample size using simple random techniques. Data were analyzed using the Multiple Regression Analysis method. Data processing using the SPSS program. The purpose of this study was to determine the factors that influence purchasing decisions at UKM Sentra Bandeng Tawang Mas Semarang. SME entrepreneurs must maintain the implementation of important factors that determine the performance of their businesses, while still making improvements to the factors that are still lacking in implementation, in order to get better performance.